Transformasi Kebudayaan: Dampak Perkembangan Teknologi dan Media Sosial - Ria Anista (Jurnal Pendidikan Sosial Indonesia, 2023)
In the era of globalization and digitalization, cultural transformation has become a significant phenomenon triggered by technological advancements and social media development. This research analyzes the impact of these changes on traditional values, social norms, individual identities, and communication patterns. A mixed-methods approach is employed, combining qualitative and quantitative analyses. Through in-depth interviews with diverse societal groups and online surveys, this study reveals that technology and social media have reshaped social interaction and communication. Traditional cultural values, such as face-to-face communication and deep interpersonal connections, have experienced a decline in priority. In contrast, digital communication and social networking have become more dominant. Social norms have also undergone changes. The exposure of personal information through social media has blurred the boundaries between private and public life. Personal identity has undergone a complex transformation; individuals can craft self-images on the virtual stage of social media, yet they also risk experiencing identity dissonance due to digital normative pressures. Communication patterns have undergone a drastic shift. Emojis, abbreviations, and images have become integral to digital language, influencing how individuals interact and communicate. While technology and social media offer benefits in global connectivity, they also pose new challenges in understanding communication nuances within evolving contexts. In conclusion, this research highlights the changes in cultural values, social norms, individual identities, and communication due to technological and social media advancements. These findings provide crucial insights into how society adapts to cultural transformations in the digital era. Understanding these changes is essential for mitigating negative impacts and maximizing the benefits offered by technological progress in daily life.